Agrobacterium tumefaciens-Mediated Transformation of Valsa mali: An Efficient Tool for Random Insertion Mutagenesis. (4th December 2013) - Wang, Caixia; Guan, Xiangnan; Wang, Hanyan; Li, Guifang; Dong, Xiangli; Wang, Guoping; Li, Baohua
Abstract : Valsa mali is a causal agent of apple and pear trees canker disease, which is a destructive disease that causes serious economic losses in eastern Asia, especially in China. The lack of an efficient transformation system for Valsa mali retards its investigation, which poses difficulties to control the disease. In this research, a transformation system for this pathogen was established for the first time using A. tumefaciens -mediated transformation (ATMT), with the optimal transformation conditions as follows: 10 6 /mL conidia suspension, cocultivation temperature 22°C, cocultivation time 72 hours, and 200  μ M acetosyringone (AS) in the inductive medium. The average transformation efficiency was 1015.00 ± 37.35 transformants per 10 6 recipient conidia. Thirty transformants were randomly selected for further confirmation and the results showed the presence of T-DNA in all hygromycin B resistant transformants and also revealed random and single gene integration with genetic stability. Compared with wild-type strain, those transformants exhibited various differences in morphology, conidia production, and conidia germination ability. In addition, pathogenicity assays revealed that 14 transformants had mitigated pathogenicity, while one had enhanced infection ability. The results suggest that ATMT of V. mali is a useful tool to gain novel insight into this economically important pathogen at molecular levels.